Inhibition of histone methyltransferase EZH2 in Schistosoma mansoni in vitro by GSK343 reduces egg laying and decreases the expression of genes implicated in DNA replication and noncoding RNA metabolism. - Adriana S A Pereira; Murilo S Amaral; Elton J R Vasconcelos; David S Pires; Huma Asif; Lucas F daSilva; David A Morales-Vicente; Vitor C Carneiro; Claudia B Angeli; Giuseppe Palmisano; Marcelo R Fantappie; Raymond J Pierce; et al. (Public Library of Science (PLoS), 2018)
BACKGROUND:The possibility of emergence of praziquantel-resistant Schistosoma parasites and the lack of other effective drugs demand the discovery of new schistosomicidal agents. In this context the study of compounds that target histone-modifying enzymes is extremely promising. Our aim was to investigate the effect of inhibition of EZH2, a histone methyltransferase that is involved in chromatin remodeling processes and gene expression control; we tested different developmental forms of Schistosoma mansoni using GKS343, a selective inhibitor of EZH2 in human cells. METHODOLOGY/PRINCIPAL FINDINGS:Adult male and female worms and schistosomula were treated with different concentrations of GSK343 for up to two days in vitro. Western blotting showed a decrease in the H3K27me3 histone mark in all three developmental forms. Motility, mortality, pairing and egg laying were employed as schistosomicidal parameters for adult worms. Schistosomula viability was evaluated with propidium iodide staining and ATP quantification. Adult worms showed decreased motility when exposed to GSK343. Also, an approximate 40% reduction of egg laying by GSK343-treated females was observed when compared with controls (0.1% DMSO). Scanning electron microscopy showed the formation of bulges and bubbles throughout the dorsal region of GSK343-treated adult worms. In schistosomula the body was extremely contracted with the presence of numerous folds, and growth was markedly slowed. RNA-seq was applied to identify the metabolic pathways affected by GSK343 sublethal doses. GSK343-treated adult worms showed significantly altered expression of genes related to transmembrane transport, cellular homeostasis and egg development. In females, genes related to DNA replication and noncoding RNA metabolism processes were downregulated. Schistosomula showed altered expression of genes related to cell adhesion and membrane synthesis pathways. CONCLUSIONS/SIGNIFICANCE:The results indicated that GSK343 presents in vitro activities against S. mansoni, and the characterization of EZH2 as a new potential molecular target establishes EZH2 inhibitors as part of a promising new group of compounds that could be used for the development of schistosomicidal agents.